Biodegradable nanoparticles obtained from zein as a drug delivery system for terpinen-4-ol - Marini,Vanderléia G. (2014)
Biodegradable nanoparticles (NPs) have received considerable attention because of their possible use in the development of strategies for the topical delivery of oils and therapeutic drugs, particularly when drug penetration in dermis is desired. Zein is a prolamine and is a promising material for the design of drug delivery systems. In this study, NPs were prepared with zein and were used to encapsulate and release terpinen-4-ol, which is a therapeutic agent for the treatment of melanoma. The results show that the zein NPs are promising nanostructured systems for the prolonged delivery of T4OL with potential applications in anti-melanoma therapy.